Aplikasi Kuesioner Kinerja Dosen Fakultas Teknik Komputer Universitas Cokroaminoto Palopo - Ramdana, R; Muliadi, M (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This study designed a questionnaire application for the performance of the Computer Science Study Program Lecturers, so that in the future the performance assessment of lecturers at the Faculty of Computer Science can be even better, so that no more difficulties are encountered in processing evaluation data or in finding lecturer evaluation data. Because basically the lecturer performance appraisal system that is currently running, there are still frequent errors in the results of the evaluation reports due to the wrong input and analysis process This application was created using Visual Basic 2010 and using the Access database. expected to help the campus in improving the performance of lecturers. The testing system used is the white box testing method.